2016
DOI: 10.5546/aap.2016.eng.114
|View full text |Cite
|
Sign up to set email alerts
|

Association between the amount of sleep and obesity in Chilean schoolchildren

Abstract: Introduction. Studies mainly performed in adults have shown an association between the amount of sleep and obesity. Objective. To determine if there is an association between nocturnal sleep deprivation during the week and the weekend, eating habits, physical activity and nutritional status among Chilean schoolchildren. Population, Material and Methods. Crosssectional study. An anthropometric assessment was done among 6-11 year-old students; the Pittsburgh Sleep Quality Index (PSQI) was used among parents to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 34 publications
0
8
1
9
Order By: Relevance
“…On average, sleeping less than 10-9 hours was associated with overweight/obesity or a higher incidence of obesity was found in short-sleepers. 6 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On average, sleeping less than 10-9 hours was associated with overweight/obesity or a higher incidence of obesity was found in short-sleepers. 6 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 …”
Section: Resultsmentioning
confidence: 99%
“…13 The studies of Guo et al 23 and Durán et al 25 had the lowest score in the quality analysis, and were considered poor, with six positive answers (in a total of 14) in the NIH tool. Most of the studies were considered fair and had between seven and nine positive answers in the NIH tool (King et al, 7 Kordas et al, 34 Christoph et al, 27 Katsa et al, 22 Carrillo-Larco et al, 16 Kordas et al, 35 Jiang et al, 21 Jong et al, 26 Hitze et al, 31 Chamorro et al, 15 Ruotolo et al, 33 Cicek et al, 20 Agüero et al, 19 Durán et al, 25 Corso et al, 24 Bazán et al, 18 Marques et al, 6 Aravena et al, 28 Giovaninni et al 29 ), and the highest quality studies were the ones made by Agüero and Riveira, 17 Golley et al 30 and Na et al, 32 with ten positive answers. The compliance with the STROBE checklist showed that only three studies fulfilled more than 75% (Agüero et al, 19 Chamorro et al 15 and King et al 7 ) of the items of the checklist, and the others accomplished between 43.7 and 71.8%.…”
Section: Resultsmentioning
confidence: 99%
“…Ao analisar as consequências nutricionais, encontrou-se que 25% (n=7) dos estudos a privação de sono em crianças e adolescentes foi fator de risco para sobrepeso e obesidade (Arora et al, 2018;Jansen et al, 2018;Chaput et al, 2011;Agüero & Rivera, 2016;Jong et al, 2012;Wang et al, 2016;Halal et al, 2015).…”
Section: Resultsunclassified
“…As evidências sugerem que a duração e a qualidade do sono bem como o sistema circadiano desempenham papéis importantes na regulação metabólica que podem predispor à obesidade (Arora & Taheri, 2015). Vale ressaltar que, o sono adequado torna-se mais essencial ainda na primeira infância e na infância para o crescimento e o desenvolvimento físico e psicossocial (Agüero & Rivera, 2016).…”
Section: Introductionunclassified
“…Em média, dormir menos de 10-9 horas foi associado com sobrepeso/obesidade, ou maior incidência de obesidade foi verificada em pessoas com sono de curta duração. 6,[15][16][17][18][19][20][21][22][23][24][25][26] Em estudo transversal realizado com 1.810 crianças de 6 a 11 anos, a qualidade do sono foi avaliada pelo questionário Pittsburgh Sleep Quality Index (PSQI), e 49,9% das crianças avaliadas dormiam menos do que o recomendado (<10 horas por dia), sendo que essa restrição de sono foi maior durante a semana e Figura 1 Fluxograma de seleção de estudos. Analisar a associação entre duração do sono e estado nutricional de crianças em idade escolar de Portugal; 829 alunos; ±9 anos.…”
Section: Métodounclassified